Remodelamento cardíaco de ratos espontaneamente hipertensos: papel do treinamento físico associado ou não com perindopril - Ligeiro, Melissa Ganeko [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Among all consequences of hypertension (HT), cardiovascular diseases are the major contributing to mortality. Factors such as cardiac hypertrophy, fibrosis and myocardium capillary density loss are involved. Spontaneously hypertensive rats (SHR) have cardiac remodeling due to hypertension and because of that, several pharmacological and non-pharmacological treatments are used. Among inhibitors of angiotensin converting enzyme (ACEi) drugs, perindopril has been shown to be efficient to improve hypertension and cardiac remodeling. Aerobic exercise training (T), on the other hand, has been used as non-pharmacological treatment of hypertension and it is also efficient to ameliorate cardiac remodeling and hypertension, however, almost nothing is known about the association of these two treatments. The objective of this present study was to analyze the effects of exercise training, associated or not with pharmacological treatment with perindopril on myocardium remodeling in SHR rats. SHR rats were divided into 5 groups: sedentary control (SC, n=12), sedentary + perindopril (SP, n=10), trained control (TC, n=13) and trained + perindopril (TP, n=14). Wistar rats were used as normotensive controls. Aerobic training was performed on a treadmill, 1h / day, 5 days / week, during 8 weeks at 60% of maximal physical capacity. SP and TP groups were daily treated with perindopril (3 mg / kg of body weight, gavage) during all experimental protocol. SC and TC groups received water. At the end of training period, pulse wave velocity and blood pressure were measured... (Complete abstract electronic acess below)

Dentre as várias consequências da hipertensão arterial (HA), as doenças cardiovasculares são as que mais matam no mundo inteiro. Fatores como hipertrofia cardíaca, aumento de fibrose e redução da densidade capilar no miocárdio estão envolvidos. Ratos espontaneamente hipertensos (SHR) desenvolvem um remodelamento cardíaco devido à HA e, neste sentido, vários tratamentos farmacológicos e não farmacológicos vêm sendo utilizados. Dentre os fármacos da classe dos inibidores da enzima conversora de angiotensina II (iECA), o perindopril tem se mostrado muito eficiente na melhora da HA e do remodelamento cardíaco. O treinamento físico (TF) aeróbio, por sua vez, vem sendo utilizado como tratamento não farmacológico, também eficaz em melhorar o remodelamento cardíaco e reduzir pressão arterial (PA), no entanto, quase nada se sabe sobre a associação desses tratamentos. O objetivo foi verificar os efeitos do TF aeróbio, associado ou não ao tratamento farmacológico com perindopril sobre o remodelamento do miocárdio de ratos espontaneamente hipertensos (SHR). Foram utilizados SHR divididos aleatoriamente em 4 grupos: sedentário controle (SC, n=12), sedentário + perindopril (SP, n=10), treinado controle (TC, n=13) e treinado + perindopril (TP, n=14). O TF aeróbio na esteira ergométrica foi de 8 semanas a 60% da capacidade máxima, 5 dias/semana. Os grupos SP e TP foram tratados com perindopril (3mg/kg por dia, via gavagem) durante todo o protocolo experimental. Os grupos SC e TC foram tratados com água... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Exercícios físicos; Inibidores enzimáticos; Coração - Hipertrofia; Hipertensão; Enzima conversora da angiotensina; Ratos endogâmicos SHR; Hypertension